Effects of adhesive materials and remnant removal techniques on dental trauma splint working time, enamel loss, and adhesive remnant index (ARI) / Zalikha Adila Zainuren - Zainuren, Zalikha Adila (2023)
The placement and removal of dental trauma splints have become a great challenge, especially in paediatric patients. Therefore, there is a need for a fast splinting procedure that allows the splint to last long for the entire splinting duration and results in less damage and less remnant left on the enamel after the removal. The purpose of this study was to evaluate the effects of different adhesive materials and remnant removal techniques on dental trauma splint working time, enamel loss, and adhesive remnant index (ARI). Eight types of adhesive materials (packable composite resin with self-etch and etch-and-rinse, flowable composite resin with self-etch and etch-and-rinse, self-cure and light-cure RMG1C, and temporary and semi permanent GIC) and six types of remnant removal techniques (white stone bur (high speed and slow speed), high-speed pointed diamond bur, high-speed tungsten carbide bur, and two types of polishing discs) were investigated. The working time during placement and removal of the splint was recorded. The ARI was determined by using the SEM microphotograph and enamel loss was measured using a contact stylus profiler. Data for the working time were analyzed with one-way ANOVA and revealed a significant difference in different groups of adhesive materials for both splint placement (p <0.001) and removal (p = 0.007). The fastest working time for placement was recorded with flowable composite resin self-etch and for removal was recorded with light-cure RMGIC. A Kruskal Wallis H test was performed for data on ARI and revealed a significant difference between different types of adhesive materials (p <0.001); the packable composite resin etch-and-rinse had the most adhesive remnants retained on the enamel surface after splint removal. No significant difference was noted in the ARI between different types of remnant removal techniques for individual adhesive materials. Data for enamel loss were analyzed with a 2-way ANOVA and showed a significant difference (p <0.001) between different groups of adhesive materials, while no significant difference (p = 0.098) was noted between different remnant removal techniques. The flowable composite resin etch-and-rinse with high-speed pointed diamond bur showed the greatest enamel loss. Meanwhile, the light-cure RMGIC group with slow-speed white stone bur resulted in the least enamel loss. Light-cure RMGIC is very favourable in terms of working time and enamel loss regardless of the remnant removal techniques. It is recommended as the material of choice for dental trauma splints in the emergency setting. Meanwhile, in a good clinical setting, the flowable composite resin self-etch can be recommended.